Stochastic optical soliton perturbations in optical metamaterial couplers with parabolic nonlocal nonlinearity and advanced dispersion analysis - Zayed, Elsayed M. E.; El-Shater, Mona; Murad, Muhammad Amin S.; Secer, Aydin; Ozisik, Muslum; Arnous, Ahmed H. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2026)
This study delves into the perturbed stochastic nonlinear Schr & ouml;dinger equation in an optical coupler for metamaterials, introducing a parabolic nonlocal law for refractive index nonlinearity, eighth-order dispersion, and multiplicative white noise. An enhanced version of Kudryashov's method, combined with the direct algebraic method, is utilized to examine stochastic effects in nonlinear optical systems. The findings reveal diverse solution types such as dark and singular solitons, Weierstrass and Jacobi doubly periodic solutions, and straddled solitons, showcasing the complex dynamics driven by nonlocal nonlinearity and higher-order dispersion under stochastic conditions. This pioneering work on the nonlinear Schr & ouml;dinger equation with a parabolic nonlocal nonlinearity and eighth-order dispersion investigates the impact of random fluctuations on nonlinear dynamics, advancing our understanding of light propagation at higher frequencies. The study aims to inspire further research into the behavior of light in unique materials and the development of more efficient light-based devices, leveraging the insights gained to innovate advanced communication tools and other optical devices, highlighting the response of these materials to random disturbances.
Keywords: Optical metamaterials; nonlocal nonlinearity; white noise; optical solitons; Kudryashov's method; direct algebraic method; DIRECTIONAL-COUPLERS; EXPANSION METHOD; Optics; Physics